Mercury(II)-catalyzed cleavage, isomerization and depurination of RNA and DNA model compounds and desulfurization of their phosphoromonothioate analogs - Saleh L.; Ora M.; Lönnberg T. (MDPI AG, 2022)
The potential of Hg(II), a metal ion so-far overlooked in the development of artificial nucleases, to cleave RNA and DNA has been assessed. Accordingly, Hg(II)-promoted cleavage and isomerization of the RNA model compound adenylyl-3′,5′-(2′,3′-O-methyleneadenosine) and depurination of 2′-deoxyadenosine were followed by HPLC as a function of pH (5.0–6.0) and the desulfurization of both diastereomers of the phosphoromonothioate analog of adenylyl-3′,5′-(2′,3′-O-methyleneadenosine) at a single pH (6.9). At 5 mM [Hg(II)], cleavage of the RNA model compound was accelerated by two orders of magnitude at the low and by one order of magnitude at the high end of the pH range. Between 0 and 5 mM [Hg(II)], the cleavage rate showed a sigmoidal dependence on [Hg(II)], suggesting the participation of more than one Hg(II) in the reaction. Isomerization and depurination were also facilitated by Hg(II), but much more modestly than cleavage, less than 2-fold over the entire pH range studied. Phosphoromonothioate desulfurization was by far the most susceptible reaction to Hg(II) catalysis, being accelerated by more than four orders of magnitude.